Infectious pancreatic necrosis virus inhibits infectious hematopoietic necrosis virus at the early stage of infection in a time dependent manner during Co-infection in Chinook salmon embryo cell lines. Issue 102 (July 2020) - Xu, Li-Ming; Liu, Miao; Zhao, Jing-Zhuang; Ren, Guang-Ming; Dong, Ying; Shao, Yi-Zhi; Lu, Tong-Yan; Zhang, Qi-Ya
Abstract: Salmonids can be co-infected by infectious hematopoietic necrosis virus (IHNV) and infectious pancreatic necrosis virus (IPNV) under natural or experimental conditions. To reveal the influence of IPNV on IHNV in co-infections, CHSE-214 cells were inoculated with IPNV at different time intervals prior to or after IHNV infection. Propagation of IHNV was determined by an immunofluorescence antibody test, real-time quantitative polymerase chain reaction, flow cytometry, and virus titration. The results showed that when cells were inoculated with IPNV prior to IHNV, IHNV multiplication was inhibited. This inhibitory effect became stronger with increasing time intervals ( P  < 0.05). When cells were inoculated with IPNV after IHNV, the inhibitory effect became weaker with increasing time intervals ( P  < 0.05), and no significant inhibition was observed at 12 h ( P  > 0.05) compared with the single IHNV infection group. The findings suggest that IHNV is inhibited at the early stage of infection by IPNV and in a time dependent manner during co-infection. Furthermore, the effect of IPNV on IHNV entry and expression of IHNV entry-related genes clathrin, dynamin-2, adaptor protein 2, and vacuolar protein sorting 35 were also determined. The results showed that IPNV did not affect the amount of IHNV entering the cells. However, the expression levels of clathrin and dynamin-2 were significantly lower in co-infection than those in single IHNV infection, which suggests that IPNV likely inhibits IHNV by affecting IHNV invasion via downregulating IHNV entry-related genes clathrin and dynamin-2 . Highlights: IPNV inhibits IHNV in a time dependent manner during co-infection in CHSE-214 cells. IPNV does not affect the amount of IHNV entering the cells in the co-infection. IHNV entry-related genes clathrin and dynamin-2 were downregulated in the co-infection. IHNV is inhibited at the early stage of infection by IPNV in the co-infection.